THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, WORK ENVIRONMENT AND ORGANIZATION COMMITMENT TOWARD JOB SATISFACTION TO INCREASE EMPLOYEES’ PERFORMANCE - Putu Sudiarta (Jurnal Ekonomi dan Bisnis Jagaditha, 2018)
The Objective of this study is to identify the effect of transformational leadership, work environment and organizational commitment toward job satisfaction and employees’ performance administration of Warmadewa University, Denpasar Bali. The research approach used was deductive quantitative approach focusing on formal and substantive theory. Hypotheses were formulated to be tested so as to empirical social reality about the employees’ performance. Data collection methods used were questionnaires distributed using Likert scale at the rating interval between 1-5 scores. The sample of the research was 62 administration employees of Warmadewa University of Denpasar Bali as respondents involved in this research. The method of analysis used to determine the relationship between variables was structural model using the method PLS (Partial Least Square) with the aid of SmartPLS 2.0 software. Key research findings included: 1. Transformational leadership has a significant negative impact on job satisfaction, 2. Work environment has an important impact on job satisfaction, 3. Organizational commitment has an important impact on job satisfaction, 4. Transformational leadership has no significant impact on performance employees, 5. Work environment does not have an important impact on employees’ performance, 6. Organizational commitment has an important impact on employee performance, 7. Job satisfaction has an important impact on employees’ performance. Discussions on the results and research findings provided further with addressable suggestions, such as the importance of paying attention to transformational leadership patterns to align in encouraging job satisfaction and employees’ performance.